The evolution of ecology in Mexico: facing challenges and preparing for the future. Issue 5 (1st June 2006) - Martínez, ML; Manson, RH; Balvanera, P.; Dirzo, R.; Soberón, J.; García-Barrios, L.; Martínez-Ramos, M.; Moreno-Casasola, P.; Rosenzweig, L.; Sarukhán, J.
Abstract : We review and analyze the historical development and challenges facing ecology as a science in Mexico, a country with limited financial and human (one scientist per 5000 inhabitants) resources and numerous environmental problems. We outline a set of research, collaborative, and financial strategies that could help to strengthen the role of ecological science in decision‐making processes, and increase cutting‐edge research, thus helping to foster economic sustainability and human well‐being in the country. Both curiosity driven and applied research will be important in this context. Interdisciplinary and inter‐institutional approaches, as well as international collaborations, are also key elements in the continued development of ecology in Mexico. Ecological knowledge is predicted to play an increasingly important role in promoting the conservation and sustainable use of Mexico's natural resources and rich biodiversity. As the history and development of ecology in Mexico parallels other Latin American countries, some of our recommendations for the future of ecology in Mexico may apply elsewhere in Central and South America.